Mechanisms of the formation of the contractile apparatus of the heart during normal development and under the influence of ethanol - Marchenko, D.G.; Cherkas Н.A.; Khripkov, I.S.; Kobeza , P.A.; Morozova , S.B. (Морфологія / Morphologia / Morfologìâ, 2022)
The review of the article is devoted to the analysis of scientific data related to the mechanism of formation of the contractile apparatus of the heart and the effect on it of such a teratogenic factor as ethanol. Chronic alcohol intoxication causes damage to almost all organs and systems of the body, including the cardiovascular system, causing significant destructive disturbances in its components. To date, there are many studies related to the study of the effect of ethanol on the myocardium [1]. Chronic alcohol intoxication is accompanied by the development of alcoholic cardiomyopathy, which in turn leads to changes in the composition of the heart muscle. Namely, alcohol consumption is associated with a violation of the contractile function of the myocardium and the development of apoptosis of cardiomyocytes. Disturbances in the synthesis of contractile proteins, such as actin and myosin, lipid metabolism and mitochondrial function, transport and binding of calcium are associated with the action of alcohol metabolite acetaldehyde. Violation of the ultrastructure of organelles after the action of ethanol on cardiomyocytes, according to many authors, is characteristic of almost all myocardial cells. The number of organelles decreased, their swelling, disorganization of their internal structure and partial lysis occurred. The largest dystrophic changes observed in the parenchyma of the rat myocardium were manifested in the mosaic structure of myofibrils, disruption of the membranes of the T-system. The process of formation of the contractile components of the myocardium and the effect of ethanol on it is studied by many researchers, however, some aspects are still open. The purpose of this work was to conduct a detailed analysis of literary sources devoted to the mechanism of development of the contractile apparatus of the heart, to analyze the effect of ethanol on the heart as a whole and on its individual contractile components.